Estilos de crianza de cuidadores y su relación con el rendimiento académico de un grupo de estudiantes de grado quinto de la institución José María Cabal del distrito de Buenaventura en el año 2020. (2020)
This research work emerged with the aim of investigating the relationship between caregiver upbringing styles and the academic performance of fifth grade students of the José María Cabal Institution of the Buenaventura District in 2020. The approach used was of a qualitative nature. With a phenomenological design, the collection of information was carried out using the technique of documents, records, materials and artifacts that allowed knowing the academic performance of the sample students of this study and the semi-structured interview where the parenting styles used by the caregivers were evidenced. For the purposes of this study, Baunrind's postulates on parenting styles were taken into account and finally it was concluded that, although there are characteristics of each parenting style in each family, there is a greater tendency towards the authoritarian and permissive parenting style and this it is related to academic performance.